Analysis of matrix and graph models of transmissions for optimization their design - Ivanov, Viktor; Urum, Galyna; Ivanova, Svitlana; Naleva, Galyna (Eastern-European Journal of Enterprise Technologies, 2017)
The application of heuristic methods in the design of transmissions is investigated. The entire path that the designer passes from the development of the design requirements, then the preliminary design and finally the development of the detailed design is considered. Heuristic methods are divided into three groups according to three design phases. For each phase, one generalized heuristic method that includes all heuristic techniques of the known methods referred to a particular group should be used when designing transmissions. Special attention is paid to the methods that use matrix and graph models. These methods are the most suitable for analyzing complex technical objects. Search for design features that are not used in right-angle gearboxes is performed by the method of creativity enhancement. Using the method of studying the structure of the problem based on the use of matrix and graph models at the phase of preliminary design, it was found that the power split in the bevel stage is possible at an angle between the axes of the bevel gear not equal to 90°. A comparative analysis of the found design with the existing gearbox at the phase of detailed design using the method of evaluating the variants for a design solution is made. Evidence of the effectiveness of heuristic methods is the development of a new gearbox design with better technical characteristics: smaller weight and dimensions. The developed heuristic methods are aimed at solving the tasks of designing transmissions; they can be used by designers, inventors and are interesting for experts in the field of heuristics.